Case Report: Diagnosis of splenic marginal zone lymphoma by ultrasound and contrast- enhanced ultrasound - Zhang, Xu; Lu, Jianghao; Hao, Yanli; Wu, Tingting; Gao, Zeyan; Zhou, Peng (Frontiers in Oncology, 2025)
Early diagnosis of splenic marginal zone lymphoma (SMZL) is difficult because of its insidious symptoms and slow progression. Combining conventional ultrasound with contrast-enhanced ultrasound can enable to differentiate between benign and malignant splenic lesions, which could guide further clinical examination and eventually improve the diagnostic rate of SMZL.